Augmentation in the treatment of restless legs syndrome with transdermal rotigotine - Beneš, Heike; García-Borreguero, Diego; Ferini-Strambi, Luigi; Schollmayer, Erwin; Fichtner, Andreas; Kohnen, Ralf (Sleep medicine, 2012)
To assess the risk of augmentation under treatment with the transdermally delivered dopamine agonist rotigotine for restless legs syndrome (RLS). Experts in RLS augmentation retrospectively reviewed data from two double-blind, placebo-controlled 6-month trials (745 rotigotine and 214 placebo subjects, NCT00136045 and NCT00135993) and from two open-label 1-year trials (620 rotigotine subjects, NCT00498108 and NCT00263068). All study visits were systematically evaluated applying the Max Planck Institute (MPI) criteria for the diagnosis of both augmentation and clinically relevant augmentation. MPI criteria for augmentation were met on at least one visit by 8.2% of all subjects in the double-blind trials with 12 subjects meeting the criteria for clinically relevant augmentation: 11 under rotigotine (1.5%) and one under placebo treatment. In the open-label trials, 9.7% of all subjects met the MPI criteria for augmentation and 2.9% met the criteria for clinically relevant augmentation. None of the patients treated with rotigotine for up to 1.5years (double-blind plus open-label trial) discontinued prematurely owing to augmentation. Neither could dose-dependency or a time pattern for clinically relevant augmentation episodes be detected. Our analyses suggest that the risk for clinically relevant augmentation for the duration of up to 18months of rotigotine treatment is low.